Applying the Technology Acceptance Model to Measure Actual Usage Decisions of Accurate Accounting Software - Yulyanah, Yulyanah; Yusuf, Yusuf (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research explores the determinants of actual usage behavior of Accurate accounting software among students in the Tax Accounting diploma program at Pamulang University. Employing the Technology Acceptance Model as the conceptual foundation, the study investigates the influence of perceived ease of use, perceived usefulness, user attitude, and behavioral intention on software adoption. Data were obtained from a group of final-year students who had prior exposure to Accurate software and were analyzed using a structural equation modeling approach with the SmartPLS application. The findings demonstrate that perceived ease of use has a significant effect on both perceived usefulness and user attitude, which subsequently shape behavioral intention and actual use. Conversely, perceived usefulness alone does not directly influence intention or usage unless mediated by attitude or behavioral factors. These results underscore the importance of strengthening user attitudes and intentions through practical and integrated learning. The study offers insights for improving digital readiness in accounting education.